2018
DOI: 10.1186/s40359-018-0233-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized control trial of computer-based training targeting alertness in older adults: the ALERT trial protocol

Abstract: BackgroundHealthy aging is associated with a decline in multiple functional domains including perception, attention, short and long-term memory, reasoning, decision-making, as well as cognitive and motor control functions; all of which are significantly modulated by an individual’s level of alertness. The control of alertness also significantly declines with age and contributes to increased lapses of attention in everyday life, ranging from minor memory slips to a lack of vigilance and increased risk of falls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Finally, as the last search was conducted in April 2018, it is possible that more recent trials were not included. We conducted a rapid literature search in PubMed in March 2020 looking for potentially relevant studies published after the last update and identified one published study [89] and six published protocols [90][91][92][93][94][95], which indicates that several trials of e-Health interventions for HA are currently ongoing. We thus recommend to update this systematic review within the next 2 years as more evidence is likely to change the conclusions of the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as the last search was conducted in April 2018, it is possible that more recent trials were not included. We conducted a rapid literature search in PubMed in March 2020 looking for potentially relevant studies published after the last update and identified one published study [89] and six published protocols [90][91][92][93][94][95], which indicates that several trials of e-Health interventions for HA are currently ongoing. We thus recommend to update this systematic review within the next 2 years as more evidence is likely to change the conclusions of the present systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…These cognitive intervention aims both to improve cognitive deficits ( Duda and Sweet, 2020 ) and to identify, track, and monitor the user’s cognitive performance ( Clare et al, 2003 ; Clare and Woods, 2004 ; Eckroth-Bucher and Siberski, 2009 ; Zelinski, 2009 ; Mowszowski et al, 2010 ; Steinerman, 2010 ; Bahar-Fuchs et al, 2013 ; Kueider et al, 2014 ; Chaikham et al, 2016 ; Lenze and Bowie, 2018 ; Gates et al, 2019 ). It has been used in persons with age-related cognitive decline ( VanVleet et al, 2018 ), mild to moderate AD ( Farina et al, 2006 ; Kanaan et al, 2014 ; Amieva et al, 2016 ; Giuli et al, 2016 ; Nousia et al, 2018 ; Liang et al, 2019 ), and loss of functionality or mild to moderate dementia, which may include structured weekly training facilitated by a therapist ( De Luca et al, 2016 ).…”
Section: Types Of Cognitive Interventionmentioning
confidence: 99%
“…Ten of the studies included were protocols, i.e., publications of study methods and planning, but not results [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . Study protocols are regularly published before the intervention is carried out so that its originality and authorship are assured, thus enabling its application by other researchers in different research centers.…”
Section: Publications Of Study Protocolsmentioning
confidence: 99%
“…Eight of the study protocols [22][23][24][25][26][27][28][29] had innovative methods and objectives, which, in general, sought to investigate the effects of multiple domain interventions focusing on a range of aspects, such as preventing cognitive impairment, cognitive functions, physical fitness, activities of daily living (ADL), quality of life, gait speed, incidence of falls, and executive functions. For these studies, participants were categorized into CN older adults, elderly at risk for cognitive impairment, subjects with aging-related cognitive impairment, and older patients diagnosed with MCI.…”
Section: Publications Of Study Protocolsmentioning
confidence: 99%